The Canadian Labour Bibliography/La Bibliographie Du Mouvement Ouvrier Canadien 1988 - Lonardo, Michael (Labour / Le Travail, 1989)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. See also the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.
Keywords: LISTS; books